PENERAPAN MODEL PEMBELAJARAN ADI (ARGUMENT DRIVEN INQUIRY) PADA KONSEP GARAM TERHIDROLISIS - Erna Dwi Susanti; Riri Aisyah; Cucu Zenab Subarkah (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Riau (UNRI), 2019)
The purpose of this study is to describe the activities of students during the learning process using the ADI model and analyze the ability of students to complete the ADI-based LKS on the concept of hydrolyzed salt. The method used in this research is class research with the design of one shoot case study. The subjects of this study were students of class XI IPA 4 in one of the 16 SMA Negeri Bandung, amounting to 37 people. The research instruments used were observation sheets, worksheets, and practicum report assessment rubrics. The results showed that student activity during learning using the ADI model reached an average of 91% and was categorized very well. The results of the research on the completion of ADI-based LKS reached an average of 73 and were categorized well, with the highest average value at the stage of revising the report, which was82. The results were obtained due to the existence of inquiry activities during the practicum and argumentation activities. Thus the ADI learning model can improve student activity and students' ability to complete ADI-based LKS on the concept of hydrolyzed salt.